PENGARUH KEADILAN ORGANISASI, SISTEM PENGENDALIAN INTERN, KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KECURANGAN (FRAUD) (Studi Empiris Pada Kantor Cabang Utama Perusahaan Leasing di Kota Pekanbaru) - Jelfani Saragih Sumbayak; Yuneita Anisma; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this reseach is to find influence of organizational justice on fraud, the influence of internal control system on fraud, and the influence of organization’s commitmen on fraud. The population in this study are employees at the main branch office of leasing in Pekanbaru City. The data used in this study in the form of primary data. Data collection techniques by distributing questionnaires to the employes who work at the main branch office of leasing in Pekanbaru City. Sample selection by simple random sampling technik. Total sample was calculated used by Slovin formula. The method of data analysis used to test the hypothesis is multiple regression analysis using the program SPSS Version 17. The result of this study is showed that organizational justice influence on fraud, internal control system inflaunce on fraud, organization’s commitment influence on fraud and leadership styles influence on fraud. The coefficient of determination in this study was 61,7%. These four variables affect the dependent variabel was 61.7%, while 38,3 % is influenced by other variabels that are not addressed in this study.Keywords: Justice, Organizational,Control, Commitmen, leadership styles and fraud